27.0k views
3 votes
Find the solution of this system of equations-6x-y=29-2x+y=19

User Motam
by
4.8k points

1 Answer

4 votes

Let's write the 2 equations:


\begin{gathered} -6x-y=29 \\ -2x+y=19​ \\ -------- \end{gathered}

We can add to eliminate "y" and solve for x first. Shown below:


\begin{gathered} -6x-y=29 \\ -2x+y=19 \\ --------- \\ -8x=48 \\ x=(48)/(-8) \\ x=-6 \end{gathered}

Now, we can plug this value of x into the first equation and solve for y. Shown below:


\begin{gathered} -6x-y=29 \\ -6(-6)-y=29 \\ 36-y=29 \\ y=36-29 \\ y=7 \end{gathered}

The solution of the system:

x = - 6

y = 7

User Weatherman
by
4.9k points